A study of dermatoses in the early neonatal period from a tertiary care hospital in North West Punjab - Shiti Bose; Emy Abi Thomas; Anuradha Bhatia; Inderpreet Sohi (Wolters Kluwer Medknow Publications, 2018)
Background: Neonatal life, as defined by the World Health Organization, constitutes the first 28 days of extrauterine life. The transition of neonatal skin from an aqueous to an air-dominant environment results in various changes, both physiological and pathological. Aims: This study was designed to find the prevalence and pattern of various physiological and pathological dermatoses as well as its relation to maternal and neonatal factors in the early neonatal period. Materials and Methods: This prospective study was done on 505 live born neonates at Christian Medical College and Hospital, Ludhiana. All consecutive live born babies and those presenting for follow-up within 7 days of birth were considered. Results: Out of 505 neonates that were examined, 284 (56.24%) were males and 221 (43.76%) were females. Physiological skin changes were seen in 460 (91.09%), the most common being physiological desquamation in 211 (41.78%) neonates followed by Milia in 199 (39.41%). Pathological changes were seen in 102 (20.20%) neonates of whom one had aplasia cutis congenita. The most common developmental abnormality was accessory nipple in 6 (1.19%) neonates. Icterus was most often seen in neonates delivered by normal vaginal delivery 134 (56.54%). Milia was more often seen in babies of multiparous mothers, 135 (67.84%) as compared to primiparous mothers. Conclusion: A good knowledge of neonatal dermatoses helps allay concerns in parents and treating physicians thereby avoiding diagnostic and therapeutic procedures, which may not be required, especially as most of the early neonatal dermatoses are transient in nature.